Social Work on Stage: Work and professional training in Brazilian sociability (Temporalis, 2026)
The article on screen is a partial result of the dissertation presented to the Graduate Program in Social Work at the Federal University of Paraíba. It aims to discuss the work of social worker and its centrality with the ethical-political project of the profession in Brazilian sociability. The research is of qualitative approach, fruit of literature review and documentary analysis, based on historical-dialectical materialism. The qualitative, practical-scientific leap of the Social Service aligned with Marxian critical social theory and the Marxist tradition is highlighted, for analysis and understanding of Brazilian capitalist sociability and its nuances, assuming the commitment to the working class meeting their needs, respecting its plurality and present particularities
Keywords: Ethical-Political Project; Sociability; Social Work